Influence of arboreal components on the physical-chemical characteristics of the soil under four silvopastoral systems in northeastern Peru - Vásquez Pérez, Héctor Vladimir; Valqui Valqui, Leandro; Bobadilla Rivera, Leidy; Arbizu Berrocal, Carlos Irvin; Alegre Horihuela, Julio; Maicelo Quintana, Jorge Luis (Elsevier, 2021)
Silvopastoral systems (SPS) are presented as an alternative for the protection and recovery of soils; however, the relationship between the tree component and the physical-chemical characteristics of the soil is unknown. Thus, the objective of this study was to evaluate the physical-chemical characteristics of the soil under four silvopastoral systems (SPS), alder (Alnus acuminata), pine (Pinus patula), cypress (Cupressus macrocarpa), and pona (Ceroxylon quindiuense), and a treeless system (TS) in the Amazonas region. A completely randomized design (CRD) with five treatments and three replicates was used. The experimental units were sampled at two depths, 0–15 and 15–30 cm. The parameters evaluated were pH, electrical conductivity (dS/m), organic matter (%), phosphorus (ppm), potassium (ppm), cation exchange capacity (meq/100 g), porosity (%), mechanical resistance (kg/cm2), bulk density (gr/cm3), moisture (%) and total carbon (t/ha). The results were analyzed by analysis of variance (α = 0.05 %) and Tukey's test of means (p ≤ 0.05). The systems presented strong acidic pH values (4.11–5.61), which resulted in high organic matter contents in all systems (6.74–9.99 %). The highest phosphorus content was in the SPS with alder (12.64 ppm), and the highest potassium content was in the SPS with cypress (382.33 ppm). Porosity in all systems was higher than 60 %. The highest bulk density was between 15 and 30 cm, and the highest percentage of moisture was in the surface layer (0–15 cm). The mechanical strength was higher in the SPS with cypress (2.62 kg/cm2). For all the systems evaluated, the highest carbon stock was found in the first 15 cm. The SPS with pine had the best soil characteristics and carbon sequestration (149.05 t/ha).